Real versus measured surface potentials in scanning Kelvin probe microscopy - Charrier, Dimitri S. H.; Kemerink, Martijn; Smalbrugge, Barry E.; Vries, Tjibbe de; Janssen, René A. J. (ACS nano, 2008)
Noncontact potentiometry or scanning Kelvin probe microscopy (SKPM) is a widely used technique to study charge injection and transport in (in)organic devices by measuring a laterally resolved local potential. This technique suffers from the significant drawback that experimentally obtained curves do not generally reflect the true potential profile in the device due to nonlocal coupling between the probing tip and the device. In this work, we quantitatively explain the experimental SKPM response and by doing so directly link theoretical device models to real observables. In particular, the model quantitatively explains the effects of the tip-sample distance and the dependence on the orientation of the probing tip with respect to the device.